Islamic Republic of Afghanistan : First Review Under the Extended Credit Facility Arrangement, Request for Waiver of Nonobservance of a Performance Criterion,Modification of Performance Criteria, and Rephasing of Disbursements Staff Report;Staff Supplement; Staff Statement; Press Release on the Executive Board Discussion;and Statement by the Executive Director for the Islamic Republic of Afghanistan. (IMF Staff Country Reports; Country Report ;, 2012)
Afghanistan's development, humanitarian, and governance challenges are formidable. Afghanistan is in its transition to become self-reliant. To achieve this goal, the government requires donor support. The IMF-supported economic program tries to address key macroeconomic challenges and seeks to safeguard the financial sector. The authorities have broadly met their program objectives, but their implementation suffered from delays. The authorities have now initiated an asset recovery process for each Kabul Bank beneficiary. The Executive Board has agreed to the authorities' request for a waiver.